Positive Solutions for Singular p-Laplacian Fractional Differential System with Integral Boundary Conditions - Liping Wang; Zongfu Zhou; Hui Zhou (Abstract and Applied Analysis)
This paper investigates the existence of positive solutions for a class of singular p-Laplacian fractional differential equations with integral boundary conditions. By using the Leggett-Williams fixed point theorem, the existence of at least three positive solutions to the boundary value system is guaranteed.